Fintech and Risk Literacy: Understanding User Awareness of Digital Financial Risks - Afrizal Afrizal (PT. Hafasy Dwi Nawasena, 2026)
The rapid growth of financial technology (fintech) has transformed financial transactions while simultaneously introducing new risks such as digital fraud, data breaches, overspending, and financial vulnerability. This study aims to analyze how users understand digital financial risks based on their level of digital financial literacy and how this understanding influences their behavior in using fintech services. The research employs a quantitative explanatory design with data collected through an online questionnaire distributed to active fintech users. The data were analyzed using Structural Equation Modeling (SEM-PLS) to examine the relationships between digital financial literacy, risk perception, and fintech usage behavior. The findings reveal that digital financial literacy has a significant positive effect on risk perception and fintech usage behavior. Risk perception also significantly influences user behavior and partially mediates the relationship between literacy and behavior. These results indicate that users with higher literacy levels are more capable of recognizing risks and engaging in more responsible and informed financial practices. In conclusion, digital financial literacy plays a critical role in shaping users’ understanding of financial risks and promoting safer, more sustainable fintech usage.